Metabolic profiles of the 30-15 intermittent fitness test and the corresponding continuous version in team-Sport athletes—elucidating the role of inter-effort recovery - Kaufmann, S.; Beneke, R.; Latzel, R.; Pfister, H.; Hoos, O. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To elucidate the role of inter-effort recovery in shuttle running by comparing the metabolic profiles of the 30-15 Intermittent Fitness Test (30-15IFT) and the corresponding continuous version (30-15IFT-CONT).